MODERN TRENDS IN INTELLIGENT CHATBOT DIGITAL VISUAL IMAGE - MA, N.; KHYNEVYCH, R. (Art and Design, 2023)
Study the digital visual image of intelligent chatbots as a sample, analyze the design trends of the digital image of chatbots and direct the design practice to improve user interaction. In the study, the method of combining literature review and empirical research is adopted. Through the analysis of existing research literature and the collection and analysis of existing design cases, the trend of digital visual image design style of intelligent chatbots is discussed. Design options for digital visual images of chatbots were analyzed, and their comparative classification was created. Based on the study of the directions of evolution of the design of the digital image of the intelligent chatbot, the main types of stylistic solutions have been determined – from traditional to abstract/anthropomorphic. The research aims to explore the latest trends and innovative design ideas in digital image design to meet the needs of users and the challenges of technological progress, create unique and attractive images of intelligent chatbots for users, and realize a new human-computer interaction experience. The results provide guidance and suggestions for innovative design of digital visuals for chatbots aimed at creating more attractive, friendly and effective digital images, as well as increasing the practical value of the application and user satisfaction of chatbots.